2014
DOI: 10.1016/j.celrep.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Benefits of Mutational Robustness in RNA Viruses

Abstract: Summary The accumulation of mutations in RNA viruses is thought to facilitate rapid adaptation to changes in the environment. However, most mutations have deleterious effects on fitness, especially so for viruses. Thus, tolerance to mutations should determine the nature and extent of genetic diversity that can be maintained in the population. Here, we combine population genetics theory, computer simulation and experimental evolution to examine the advantages and disadvantages of tolerance to mutations, also kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 64 publications
2
55
0
1
Order By: Relevance
“…As has been suggested for DENV (Sim et al, 2015), the immediate deleterious effects of bottlenecks and high mutation rates appeared to be avoided by WNV through the rapid recovery of viral genetic diversity during intra-tissue replication. However, rapidly expanding populations and high multiplicities of cellular infection (MOIs) may allow mosquito tissues to tolerate new mutations, which could be either costly or beneficial in a new environment (Stern et al, 2014). Surprisingly, we detected a severely lower competitive fitness of the saliva derived WNV populations relative to the input virus in avian cells.…”
Section: Discussionmentioning
confidence: 99%
“…As has been suggested for DENV (Sim et al, 2015), the immediate deleterious effects of bottlenecks and high mutation rates appeared to be avoided by WNV through the rapid recovery of viral genetic diversity during intra-tissue replication. However, rapidly expanding populations and high multiplicities of cellular infection (MOIs) may allow mosquito tissues to tolerate new mutations, which could be either costly or beneficial in a new environment (Stern et al, 2014). Surprisingly, we detected a severely lower competitive fitness of the saliva derived WNV populations relative to the input virus in avian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although experimentally measuring robustness in virus populations can be complex, competition experiments in vesicular stomatitis virus have shown that a more mutationally robust virus lineage can have an advantage over a faster-replicating lineage when the mutation rate is increased via a mutagen (134). This work, combined with theoretical studies, suggests that natural selection can favor mutational robustness in viral populations (135) and can even facilitate adaptation to a novel host under certain conditions (110).…”
Section: Mutational Robustnessmentioning
confidence: 96%
“…Although robustness may increase the likelihood of producing a variant with an expanded host range, the success of this variant relies on how well it can adapt to the new host. Because robustness can either hinder or facilitate adaptation, depending on various conditions, the role of robustness in host range expansion is complex (110,146). Further experimental studies are needed both to confirm the mutational robustness of coronaviruses and to determine its contribution to host range expansion.…”
Section: Mutational Robustnessmentioning
confidence: 98%
See 1 more Smart Citation
“…Like other RNA viruses, genetic diversity is rapidly formed by error-prone polymerases (~10 −4 /site/round of replication [1214]), which seem to operate at optimal fidelity [1517]. Collectively, intrahost virus variants influence population fitness [18,19], alter disease outcome [20,21], and provide opportunities for adaptation [22,23]. However, the relationships between viral genetic diversity and phenotype become muddled once the temporal aspects of evolution are included: Viral populations are in constant flux.…”
Section: Introductionmentioning
confidence: 99%